Shortcomings in the Legal System on Securities in Vietnam - Vinh Hung, Nguyen; Thinh, Tran Cong; Hoi, Dao Xuan (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
Vietnam's stock market has overgrown and attracted an increasing number of investors. However, among various factors that affect the investors' participation, psychological ones play a crucial role. In more than 20 years of development, the legal system on securities in Vietnam has exposed several limitations and inadequacies that result in inefficient operation of the stock market and unsafely for domestic and foreign investors. Therefore, the Article will study the shortcomings of the legal system on securities of Vietnam and propose some solutions to ensure the safety of investors in Vietnam's stock market participation. To research the psychological factors of stock investment in Vietnam, the authors combine the method of collecting and analyzing information (data). The primary research method used in this Article is collecting secondary data from the collected data. In general, the paper synthesizes data from many sources of information that the author's team can obtain and continuously analyzes tests, compares, and evaluates to identify the fundamental problems for studying. In addition, to approach the research subjects, the Article also uses a combination of popular research methods of economic fields such as statistical method, comparative method, economic efficiency analysis method, and descriptive method to analyze, evaluate and forecast the psychological factors of securities investment affecting Vietnam's stock market. According to the results, authors have given two main groups of solutions: Dealing with inaccurate information that affects the transparency of the stock market; and building and perfecting Vietnam's securities legal system.